Preparation method of water oxidation electrode with surface containing NiFe2O4 microspheres
Through the water heat treatment of the stainless steel mesh, the water oxidation electrode containing Nife2O4 micromi balls is prepared, which solves the problem of high cost and complex preparation of existing water oxidation electrode materials. Water hydrogen application.
Patent Information
- Application Number
- CN202411473744.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2025-01-24
AI Technical Summary
The existing water oxidation electrode materials have high cost, complex preparation processes and inefficient kinetic problems in the process of electrolyzing water hydrogen production, and are difficult to be widely used in large-scale industrial applications.
By surface modification of the stainless steel mesh and hydrothermal reaction using a mixed aqueous solution of H2O2 and KOH, a water oxidation electrode containing NiFe2O4 microspheres on the surface was successfully prepared. This method has simple operation, low cost, wide sources of raw materials, and good long-term stability under alkaline conditions.
The prepared water oxide electronics have excellent OER water oxidation performance, low potential, good stability, and suitable for large -scale hydrogen -making fields.
Smart Images

Figure CN119352083A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electrocatalysts, and in particular relates to a method for preparing a water oxidation electrode with NiFe2O4 micron balls on the surface. Background Art
[0002] At present, hydrogen energy is a hot spot in energy utilization, which is mainly due to its many advantages such as high energy density and pollution-free. The combustion heat of hydrogen energy is as high as 285.8kJ / mol, and the only product of its combustion is water. It does not produce pollutants such as CO2 and nitrogen oxides. It is a truly clean energy. Although hydrogen energy has many advantages, it is easily restricted by raw materials in its production process. Due to different hydrogen raw materials, industrial hydrogen production currently mainly uses three process technologies: fossil energy hydrogen production process, biomass hydrogen production process and water decomposition hydrogen production process. Although fossil energy such as coal, crude oil and natural gas are currently the main raw materials for hydrogen production, with the gradual depletion of these non-renewable resources and the increasingly serious environmental pollution problems, this method of hydrogen production based on non-renewable fuels is difficult to sustain. Therefore, in the short term in the future, it is likely to be replaced by sustainable and cleaner hydrogen production methods.
[0003] Since water is abundant in nature, hydrogen can be produced by electrolysis of water. Using water to produce hydrogen not only has sufficient raw materials but also does not pollute the environment, which creates favorable conditions for the large-scale application of hydrogen energy. At present, the technology of hydrogen production by electrolysis of water has been applied on a large scale in industry. The process of water electrolysis includes two reactions, namely the hydrogen evolution reaction (HER) at the cathode and the oxygen evolution reaction (OER) at the anode. The oxygen evolution reaction is a four-electron, four-proton transfer process. Compared with the hydrogen evolution reaction, it is a slow kinetic process and requires a large overpotential. Therefore, how to improve the electrocatalytic performance of the oxygen evolution reaction is the key to hydrogen production by electrolysis of water.
[0004] At present, the research on water oxidation electrode materials mainly focuses on precious metals and their alloys, non-precious metals and transition metal oxides. Among them, precious metal catalysts include platinum (Pt), palladium (Pd), etc. Precious metal catalysts usually have efficient OER catalytic performance and excellent stability. However, due to high cost and limited earth reserves, their large-scale application in the field of water decomposition is limited; transition metal catalysts mainly include iron (Fe), cobalt (Co), nickel (Ni), etc. Although transition metal catalysts are inexpensive, their preparation process is complicated and there are also certain difficulties in practical applications.
[0005] In recent years, Ni-Fe-based composite materials have attracted widespread attention due to their low overpotential and high activity, and are considered to be the most promising earth-abundant OER electrocatalysts in alkaline environments. A series of studies have shown that when the nickel content on the surface of Ni-Fe composite materials is in the range of 45-90% (atomic content), it exhibits excellent water oxidation performance. On the other hand, stainless steel is an industrial alloy with iron, nickel and chromium as the main components. It has the advantages of low cost, good mechanical strength, hardness and chemical stability, and has the potential to become a water oxidation catalyst. In addition, a large amount of stainless steel waste is generated every year, which greatly wastes resources.
[0006] Based on this, the inventors intend to perform surface modification on stainless steel mesh, which is low-cost and contains a large amount of water oxidation active elements (such as Ni, Fe, Cr, etc.), to prepare water oxidation electrodes, thus creating the possibility for large-scale industrial application of stainless steel OER electrodes. Summary of the invention
[0007] The purpose of the present invention is to solve the shortcomings of the above-mentioned existing water oxidation electrode materials and provide a method for preparing a water oxidation electrode containing NiFe2O4 micron balls on the surface. The method is simple to operate, low in cost, and has a wide source of raw materials. The prepared water oxidation electrode has good OER water oxidation performance and has long-term good stability under alkaline conditions.
[0008] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0009] A method for preparing a water oxidation electrode having NiFe2O4 micron balls on its surface comprises the following steps:
[0010] (1) cutting the stainless steel mesh into electrode sheets of suitable size, and then placing them in a hydrochloric acid solution for ultrasonic treatment, taking them out after the treatment, washing them and vacuum drying them to obtain a stainless steel mesh blank substrate;
[0011] (2) immersing a stainless steel mesh blank substrate in a reactor containing a mixed aqueous solution of H2O2 and KOH, sealing the reactor and placing it in an oven for hydrothermal reaction at 120-180°C for 4-8 hours, cooling to room temperature after the reaction, taking it out, cleaning it, and drying it to obtain a water oxidation electrode containing NiFe2O4 microspheres on the surface;
[0012] In step (2), in the mixed aqueous solution of H2O2 and KOH, the concentration of H2O2 is 0.05-0.25 mol / L, and the concentration of KOH is 0.5-2 mol / L.
[0013] Furthermore, in step (1), the concentration of the hydrochloric acid solution is 1 mol / L, and the ultrasonic treatment time is 12 to 18 minutes.
[0014] Furthermore, in step (1), the cleaning is first performed with deionized water, then ultrasonically cleaned with anhydrous methanol and acetone in sequence, and finally rinsed with deionized water.
[0015] Furthermore, in step (2), in the mixed aqueous solution of H2O2 and KOH, the concentration of H2O2 solution is 0.20 mol / L, and the concentration of KOH is 1 mol / L.
[0016] Furthermore, in step (2), the temperature of the hydrothermal reaction is 150° C. and the time is 5 hours.
[0017] Beneficial effects of the present invention:
[0018] The present invention provides a method for preparing a water oxidation electrode containing NiFe2O4 micron balls on the surface. With a stainless steel mesh as a substrate and KOH and H2O2 as etching solutions, a low-cost and efficient water oxidation electrode is successfully prepared by a hydrothermal method in an alkaline environment. NiFe2O4 is newly generated on the surface of the water oxidation electrode. A series of electrochemical tests and characterization methods are performed, indicating that the prepared water oxidation electrode has excellent OER performance. The preparation method of the present invention is simple to operate, low in cost, and has a wide source of raw materials. The prepared water oxidation electrode has good OER water oxidation performance and has long-term good stability under alkaline conditions, and has broad application prospects in the field of large-scale hydrogen production. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 XRD patterns of water oxidation electrodes prepared in Example 1 and Comparative Example 1;
[0020] Figure 2 The XPS test results of the water oxidation electrodes prepared in Example 1 and Comparative Example 1;
[0021] Figure 3 The SEM images of the water oxidation electrodes prepared in Example 1 and Comparative Example 1;
[0022] Figure 4 LSV curves of the water oxidation electrodes prepared in Examples 1-6;
[0023] Figure 5 LSV curves of the water oxidation electrodes prepared in Example 1 and Comparative Example 1;
[0024] Figure 6 EIS graphs of water oxidation electrodes prepared in Example 1 and Comparative Example 1;
[0025] Figure 7 The stability test results of the water oxidation electrode prepared in Example 1;
[0026] Figure 8CV curves and ECSA diagrams of the water oxidation electrodes prepared in Example 1 and Comparative Example 1 at different scanning rates. DETAILED DESCRIPTION
[0027] The technical solution of the present invention is clearly and completely described below in conjunction with the accompanying drawings and specific embodiments.
[0028] In the following embodiments, the stainless steel mesh used is model 304, and the XPS measured main component contents are: nickel 4.4%, chromium 18.34%, and iron 77.3%. However, this is not limited to this.
[0029] Example 1
[0030] A method for preparing a water oxidation electrode having NiFe2O4 micron balls on its surface comprises the following steps:
[0031] (1) Cut the stainless steel mesh into electrode sheets with a size of 20 mm × 5 mm × 1 mm, and then place them in a 1.0 mol / L hydrochloric acid solution for ultrasonic treatment for 15 min. After the treatment, take them out, wash them with deionized water for 10 min, then use anhydrous methanol and acetone for ultrasonic cleaning for 5 min each, and finally rinse them with deionized water and vacuum dry them at 60°C for 2 h to obtain a blank stainless steel mesh substrate;
[0032] (2) The stainless steel mesh blank substrate was immersed in a reactor containing 7 mL of H2O2 and KOH (in the mixed aqueous solution, the concentration of H2O2 was 0.20 mol / L and the concentration of KOH was 1 mol / L). The reactor was sealed and placed in an oven for hydrothermal reaction at 150°C for 5 h. After the reaction was completed, it was cooled to room temperature and taken out and cleaned with deionized water, anhydrous methanol and acetone in turn. After drying, a water oxidation electrode containing NiFe2O4 microspheres on the surface was obtained.
[0033] Example 2
[0034] In step (2), the hydrothermal reaction temperature is 120° C., and the rest is the same as in Example 1.
[0035] Example 3
[0036] In step (2), the hydrothermal reaction temperature is 140° C., and the rest is the same as in Example 1.
[0037] Example 4
[0038] In step (2), the hydrothermal reaction temperature is 160° C., and the rest is the same as in Example 1.
[0039] Example 5
[0040] In step (2), the hydrothermal reaction temperature is 170° C., and the rest is the same as in Example 1.
[0041] Example 6
[0042] In step (2), the hydrothermal reaction temperature is 180° C., and the rest is the same as in Example 1.
[0043] Comparative Example 1
[0044] The stainless steel blank substrate is used as the water oxidation electrode. The preparation method of the stainless steel blank substrate is the same as step (1) in Example 1.
[0045] Figure 1 The XRD patterns of the water oxidation electrodes prepared in Example 1 and Comparative Example 1 show that, compared with the stainless steel mesh blank substrate, the water oxidation electrode prepared in Example 1 has several more diffraction peaks, among which the diffraction peaks at the crystal planes (104), (110), (202) and (116) are significantly enhanced, corresponding to the substance Fe2O3 (PDF card number 89-0598); in addition, two diffraction peaks are added at the crystal planes (311) and (422), matching the substance NiFe2O4 (PDF card number 71-0852); therefore, the XRD test results show that, after the hydrothermal reaction, the stainless steel mesh blank substrate has produced new metal oxides Fe2O3 and NiFe2O4 on its electrode surface.
[0046] Figure 2 The XPS test results of the water oxidation electrodes prepared in Example 1 and Comparative Example 1 are shown in FIG. Figure 2 (a) Fe2p 3 / 2 picture, Figure 2 (b) is the O1s diagram, Figure 2 (c) Ni 2p 3 / 2 picture, Figure 2 (d) is Cr 2p 3 / 2 picture, Figure 2 (e) is a full spectrum. Through the analysis of X-ray photoelectron spectroscopy (XPS), it can be seen that although the stainless steel mesh blank substrate and the water oxidation electrode prepared in Example 1 both contain Cr, Fe, and Ni metal elements, compared with the stainless steel mesh blank substrate, the Cr content detected in the water oxidation electrode prepared in Example 1 is reduced, and Fe 0 The composition of iron is reduced, and more of it is converted into iron oxide; such as Figure 2 (d) Two groups of Cr peaks on the stainless steel mesh blank substrate, Cr 0 (576.5eV) and Cr 3+ (586.7 eV), corresponding to the Cr on the water oxidation electrode prepared in Example 1 0 With Cr 3+ The content is significantly reduced, and the Cr element is reduced after the surface is hydrothermally treated; Figure 2 (a), Fe on stainless steel mesh blank substrate 0The content of Fe is relatively high, but there is Fe on the water oxidation electrode prepared in Example 1. 2+ (710.3eV), Fe 3+ (713.2eV) and other signal peaks, a large amount of Fe 0 Transformed into +2 and +3 valence iron ions; Figure 2 (b) is the O1s spectrum, where O 2- (529.0-529.8eV), OH - (530.7-531.5 eV) and H2O (532.2-533.6 eV); Figure 2 (c) Ni2p 2 / 3 The Ni content on the surface of the stainless steel mesh blank substrate is relatively low, while in the spectrum of the water oxidation electrode prepared in Example 1, multiple Ni 2+ (855.7eV), (861.6eV), (872.7eV) peaks.
[0047] Figure 3 The SEM images of the water oxidation electrodes prepared in Example 1 and Comparative Example 1 are shown in FIG. Figure 3 (a) Figure 3 (b) is the SEM image of the stainless steel mesh blank substrate prepared in Comparative Example 1 at different scales. Figure 3 (c) Figure 3 (d) is the SEM image of the water oxidation electrode prepared in Example 1 at different scales. It can be seen that the stainless steel mesh without hydrothermal corrosion is made of stainless steel wires interwoven and has a relatively smooth surface. However, the treated sample (water oxidation electrode prepared in Example 1) has a large number of steamed bun-shaped micron particles growing on the electrode surface. These newly generated micron particles create more active sites and specific surface area than the original smooth SSM, thereby reducing the overpotential of OER and improving the electrode catalytic performance. Combined with the characterization analysis of XRD, it can be seen that the micron particles are mainly attributed to the metal oxide NiFe2O4.
[0048] 1. After the water oxidation electrode containing NiFe2O4 microspheres on the surface prepared in Example 1-6 was activated, LSV (linear sweep voltammetry) was performed using an electrochemical workstation.
[0049] Figure 4 The LSV curves of the water oxidation electrodes prepared in Examples 1-6 show that when the H2O2 solution concentration is the same and the hydrothermal reaction time is the same, when the reaction temperature is 150°C (Example 1), the electrochemical performance of the water oxidation electrode material is the best, and its electrochemical performance is the best at 10 mA cm -2At the current density of , the overpotential is the lowest, which is 176mV. As the potential increases, small bubbles continue to appear on the surface of the water oxidation electrode, and the curve gradually changes from gentle to steep.
[0050] Figure 5 The LSV curves of the water oxidation electrodes prepared in Example 1 and Comparative Example 1 are shown in FIG. Figure 5 (a) is the LSV curve, Figure 5 (b) is the corresponding Tafel slope diagram, Figure 5 (a) It can be seen that compared with the stainless steel blank substrate without hydrothermal treatment, the water oxidation performance of the water oxidation electrode prepared in Example 1 shows a significant upward trend. -2 At the current density, its value is only 176mV, which is 177mV lower than that of the stainless steel blank substrate. The overpotential of the water oxidation electrode prepared in Example 1 is 100mA cm -2 The current density is only 227mV; Figure 5 (b) It can be seen that the Tafel slope of the water oxidation electrode prepared in Example 1 is 22.8 mV dec. -1 , which is lower than the Tafel slope of the stainless steel blank substrate without hydrothermal treatment, which is 47.9 mV dec. -1 This shows that the water oxidation electrode prepared in Example 1 of the present invention has better electrochemical performance, faster catalytic rate, good electrochemical kinetic performance, and is an excellent OER catalytic electrode material.
[0051] 2. Electrochemical impedance spectroscopy (EIS) test was performed on the water oxidation electrodes prepared in Example 1 and Comparative Example 1.
[0052] Figure 6 3 and 4. The EIS graphs of the water oxidation electrodes prepared in Example 1 and Comparative Example 1 show that the radius of the water oxidation electrode in the semicircular region of Example 1 is significantly smaller than that of the stainless steel mesh blank substrate that has not been hydrothermally treated, indicating that the conductivity and mass transfer rate of the prepared electrode have been significantly improved after hydrothermal treatment.
[0053] 3. The stability test of the water oxidation electrode prepared in Example 1 and containing NiFe2O4 microspheres on the surface was carried out.
[0054] Test method: In order to test the stability of the prepared electrode, constant current electrolysis was carried out in a 1.0 mol / L KOH aqueous solution with a current density of 10 mA cm -2 The overpotential was recorded for 20 hours and its change over time was observed. Then, the Origin software was used to draw a graph to observe the change in the overpotential. -2The segmented constant current electrolysis (ISTEP) test was carried out within the current density range. The electrolysis was performed for half an hour under each current density condition to observe the change in the overpotential.
[0055] Figure 7 The stability test results of the water oxidation electrode prepared in Example 1 are as follows: Figure 7 (a) is the result of long-term chronopotentiometry test. Figure 7 (b) is the test result of segmented constant current electrolysis (ISTEP). It can be seen that the water oxidation electrode prepared in Example 1 can -2 It can work stably and continuously for 20 hours at a current density of , and there is no obvious fluctuation in the overpotential, which proves its excellent stability; the test results of segmented constant current electrolysis (ISTEP) show that after half an hour of electrolysis under each current density condition, there is no obvious change in the overpotential, which further confirms its long-term stability.
[0056] 4. Cyclic voltammetry (CV) tests were performed on the water oxidation electrode prepared in Example 1 and the stainless steel blank substrate prepared in Comparative Example 1 in 1 M potassium hydroxide at a voltage range of 1.0768-1.1248 (V vs. RHE) at a scan rate of 10 mV s -1 Increase to 100mV s -1 and calculate the double layer capacitance (C dl ) was used to evaluate the electrochemically active area (ECSA) of the material.
[0057] Figure 8 The CV curves and ECSA diagrams of the water oxidation electrodes prepared in Example 1 and Comparative Example 1 at different scanning rates are shown, wherein: Figure 8 (a) is the CV curve of the water oxidation electrode prepared in Example 1 at different scanning rates, Figure 8 (b) is the CV curve of the water oxidation electrode prepared in Comparative Example 1 at different scanning rates, Figure 8 (c) is the ECSA graph. It can be seen that compared with the stainless steel blank substrate, the CV area of the water oxidation electrode prepared in Example 1 is larger. On this basis, the CV curves of the two are processed by origin to obtain C dl , we can get the C of the sample before and after treatment dl The relationship is: the water oxidation electrode prepared in Example 1 (0.84mF cm -2 )>Stainless steel blank substrate (0.17mF cm -2 ), based on which it can be calculated that the electrochemical surface area (ECSA) of the water oxidation electrode prepared in Example 1 is 4.94 times that of the stainless steel blank substrate, confirming that the active sites of the water oxidation electrode prepared in Example 1 are increased and have better OER water oxidation performance.
Claims
1. A method for preparing a water oxidation electrode having NiFe2O4 microspheres on its surface, characterized in that: The steps include: (1) cutting the stainless steel mesh into electrode sheets of suitable size, and then placing them in a hydrochloric acid solution for ultrasonic treatment, taking them out after the treatment, washing them and vacuum drying them to obtain a stainless steel mesh blank substrate; (2) immersing a stainless steel mesh blank substrate in a reactor containing a mixed aqueous solution of H2O2 and KOH, sealing the reactor and placing it in an oven for hydrothermal reaction at 120-180°C for 4-8 hours, cooling to room temperature after the reaction, taking it out, cleaning it, and drying it to obtain a water oxidation electrode containing NiFe2O4 microspheres on the surface; In step (2), in the mixed aqueous solution of H2O2 and KOH, the concentration of H2O2 is 0.05-0.25 mol / L, and the concentration of KOH is 0.5-2 mol / L.
2. The method for preparing a water oxidation electrode having NiFe2O4 microspheres on its surface as claimed in claim 1, characterized in that: In step (1), the concentration of the hydrochloric acid solution is 1 mol / L, and the ultrasonic treatment time is 12 to 18 minutes.
3. The method for preparing a water oxidation electrode having NiFe2O4 microspheres on its surface as claimed in claim 1, characterized in that: In step (1), the cleaning is first performed with deionized water, then ultrasonically cleaned with anhydrous methanol and acetone in sequence, and finally rinsed with deionized water.
4. The method for preparing a water oxidation electrode having NiFe2O4 microspheres on its surface as claimed in claim 1, characterized in that: In step (2), in the mixed aqueous solution of H2O2 and KOH, the concentration of H2O2 is 0.20 mol / L, and the concentration of KOH is 1 mol / L.
5. The method for preparing a water oxidation electrode having NiFe2O4 microspheres on its surface as claimed in claim 1, 2, 3 or 4, characterized in that: In step (2), the temperature of the hydrothermal reaction is 150° C. and the time is 5 hours.